A new species of the gobiid genus Priolepis (Teleostei:Gobiidae) from Taiwan - Chen, I-Shiung; Chen, Jie-Ting; Harefa, Tonisman (Zootaxa, 2024)
A gobiid genus Priolepis is described from coastal waters off Taiwan. The new species is belonging to Group III of Priolepis group that characterized by reduced pattern of transverse cheek papillae and the presence of predorsal scales. The new species Priolepis formosa sp. nov, is readily distinguished from congeners by the following unique combinations of characters: (1) fin counts D2 I/9, A I/7–8 (modally 8), P 17–19 (modally 18). (2) Squamation 25–27 (modally 26), TR 7–8 (modally 8), PreD 6–8 (modally 8); having no scales on cheek, opercle. (3) Head with reduced transverse papillae. (4) distinctive coloration: body light brown with scale pockets strongly outlined with melanophores, middle opercle with a vague reddish-pink pupil-sized blotch.